Perspektif Mahasiswa Akuntansi Terhadap Faktor-Faktor Penentu Karirnya Sebagai Auditor Pemerintah - Globi Ukhra; Muamar Nur Kholid; Selfira Salsabilla (Jurnal Proaksi, 2024)
Data shows that the need for government auditors continues to increase from year to year. This article examines the internal factors that influence the intention of accounting students to become government auditors in Indonesia. This article uses Social Cognitive Career Theory as a research framework. The internal factors included in this article are self-efficacy and outcome expectation. The population in this study consists of Accounting students in Yogyakarta. The sampling technique employed is purposive sampling, and a total of 170 active Accounting students are used as the sample for the study. The study employs a quantitative research approach, utilizing Partial Least Square (PLS) analysis as the chosen analytical method.The results show that there is a significant influence of self-efficacy and outcome expectation on the intention of accounting students to become government auditors. The results of this study can contribute to the education providers to give more massive exposure to their students to encourage them to choose and contribute linearly with their main discipline, especially to become government auditors.